PERLINDUNGAN HUKUM PEREMPUAN KORBAN KEKERASAN SEKSUAL YANG MENGALAMI BLAMING THE VICTIM DI TINJAU DARI PERSPEKTIF VIKTIMOLOGI - Muhammad Amin; Andri Nurkartiko (UNES Law Review, 2023)
Sexual violence is a form of human rights abuse. This explicitly strips women of their constitutionally guaranteed civil right to safety and security, Article 28G(1) of the Constitution. Many women victims lose their right to recognition, security, protection, assurance of a fair trial and equal treatment before the law because they do not receive a fair trial. The purpose of this article is to first understand and explore the idea of ​​legal protection for female victims of sexual violence in Indonesia. Second, to determine the extent to which Indonesian law applies to the legal protection of female victims of rape. Attitudes and judgments toward victims are often at the root of sexual violence. It is therefore interesting to study victimology as part of criminal law. Victim blaming he can monitor and deal with in two ways (2). The first examines the impact of victim, perpetrator, and contextual characteristics on negative attitudes about sexual violence. The second approach focuses on investigating the relationship between victim blaming and victims of sexual violence. This type of research employs normative appraisals, and legal studies focuses on the study of legal provisions and includes jurisprudence, which consists of dogmatic studies of law, legal theory, and legal philosophy. The study concludes that the basic idea behind the emergence of victim-blaming legal protection for victims is the provision of Article 27 of the 1945 Second Amendment to the Constitution, namely that all citizens before the law. It is a recognition of equality of On the other hand, Indonesia has long had positive laws providing legal protection for victims of sexual violence. However, many laws and regulations in Indonesia do not contain provisions specifically aimed at victims of sexual violence who are victims of referrals.